Dampak Implementasi Sistem Coretax di Kantor Wilayah Direktorat Jenderal Pajak Sulawesi Utara, Tengah, Gorontalo, dan Maluku Utara terhadap Kepatuhan Wajib Pajak Pengusaha Kena Pajak - Sheila Fitriana Mashanafi; Yuli Rawun; Alfian Maase (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The digital transformation of taxation through the implementation of the Coretax Administration System (CTAS) represents an effort to modernize tax administration in order to improve service effectiveness and taxpayer compliance. This study aims to analyze the impact of Coretax implementation on the compliance of Taxable Entrepreneurs (Pengusaha Kena Pajak/PKP) at the Regional Office of the Directorate General of Taxes for North Sulawesi, Central Sulawesi, Gorontalo, and North Maluku (Kanwil DJP Suluttenggomalut). A qualitative approach with a descriptive method was employed, with data collected through in-depth interviews, observation, and documentation involving tax officers and PKP taxpayers who directly utilized the Coretax system. The findings indicate that Coretax implementation positively affects taxpayer compliance, particularly in improving reporting timeliness, data accuracy, and the accessibility of integrated tax services, although challenges remain in the form of server instability, limited digital literacy, and the adaptation process required of users. The implementation of Coretax is considered effective in supporting taxpayer compliance and encouraging voluntary compliance, so that system improvement, broader socialization, and stronger technical support are still needed to optimize its implementation.